Technical descriptions of four hemispherectomy approaches: From the Pediatric Epilepsy Surgery Meeting at Gothenburg 2014. (April 2017) - Baumgartner, James E.; Blount, Jeffrey P.; Blauwblomme, Thomas; Chandra, P. Sarat
Summary: Hemispherectomy is a complex multistep procedure with a steep learning curve. Several surgical approaches have been developed, but each requires considerable practice to master. Four experienced pediatric neurosurgeons, who participated in the 2014 Gothenburg Pediatric Epilepsy Surgery Meeting, provided succinct technical summaries of four hemispherectomy approaches: modified functional hemispherectomy, peri‐insular hemispherotomy, parasagittal hemispherotomy, and endoscopic‐assisted hemispherotomy. No clinical or outcome data are included. Our intention is to reduce the slope and length of the learning curve for surgeons and to improve the understanding of the technical details of hemispherectomy surgery by nonsurgeonmembers of epilepsy teams.